Pemberdayaan Lembaga Bundo Kanduang di Nagari Melalui Kebijakan Pembangunan yang Responsif Gender - Sri Yunarti (Kafa`ah: Journal of Gender Studies, 2017)
Minangkabau traditional institutions have sociological and psychological relationship with the local community. In West Sumatra, known as Bundo institutions Kanduang a custom isntitusi driven by women in addressing the problems of households, women and children. Potentially progress or setbacks half of an area determined by the progress and setbacks of women. Various development policies in many areas have yet to put women as subjects of development. Development policies that there is not yet considering the condition of the position and needs of women, both practical and strategic. Many of the problems faced by women in the scope of Bundo Kanduang institution as a result of cultural and structural in society. Bundo institutions Kanduang in Nagari as a base empirically women empowerment development. just a sub-section of institutions that deal with social issues, youth, and women are still the strong gender bias both political elites, government and community leaders. At least the figures of women who are able to act as agents for the empowerment of women in Nagari level.